2019
DOI: 10.1111/ina.12622
|View full text |Cite
|
Sign up to set email alerts
|

Humidity control effect of vapor‐permeable walls employing hygroscopic insulation material

Abstract: Airtight construction and high‐performance thermal insulation materials are commonly considered important building features to enhance indoor thermal comfort while reducing thermal load. However, when water vapor is generated in such airtight indoor spaces, it cannot be discharged to the outside, causing interstitial condensation and subsequent intrusion of moisture into the walls. Hygroscopic building materials such as cellulose fiber insulation (CFI), characterized by high water capacity, are a potential cou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 17 publications
0
6
0
Order By: Relevance
“…In the design and construction of buildings, the use of constructive elements with high performance in thermal insulation is necessary to improve energy efficiency, which produces environmental, economic and social benefits [1]. However, increasing hermeticism can generate severe changes in the migration of moisture in the internal spaces, which, due to its inability discharge to the outside, causes problems of surface and interstitial condensation [2,3]. This condensation phenomenon is associated with an increase in the thermal conductivity of the materials, which decreases their capacity as an insulator [4], and the deterioration and appearance of mould that affects the health of the occupants [5].…”
Section: Introductionmentioning
confidence: 99%
“…In the design and construction of buildings, the use of constructive elements with high performance in thermal insulation is necessary to improve energy efficiency, which produces environmental, economic and social benefits [1]. However, increasing hermeticism can generate severe changes in the migration of moisture in the internal spaces, which, due to its inability discharge to the outside, causes problems of surface and interstitial condensation [2,3]. This condensation phenomenon is associated with an increase in the thermal conductivity of the materials, which decreases their capacity as an insulator [4], and the deterioration and appearance of mould that affects the health of the occupants [5].…”
Section: Introductionmentioning
confidence: 99%
“…However, optimal energy consumption is not the only concern of advanced design methods applied in the building sector, and other factors should be taken into account [ 16 , 17 , 18 , 19 ]. Besides the thermal performance of building envelopes, maintenance of optimal indoor air quality without excessive or insufficient levels of humidity has to be considered as well [ 20 , 21 , 22 ]. The previous research studies showed that an optimal level between 40% and 60% relative humidity (RH) is needed to ensure the well-being and health of building occupants [ 23 , 24 ].…”
Section: Introductionmentioning
confidence: 99%
“…The particular importance of indoor moisture level is shared by issues such as furniture durability and health issues. To be more specific, plasters with lightweight aggregate, silica gel, minerals, and charcoals have been designed and consequently studied to provide satisfactory indoor humidity control [14][15][16][17]. In this regard, the effect of total pore volume, shape, and pore size distribution were found to be promising research lines towards the passive modulation of indoor relative humidity [18].…”
Section: Introductionmentioning
confidence: 99%